Faktor-Faktor Yang Mempengaruhi Persepsi Wajib Pajak Mengenai Etika Atas Penggelapan Pajak (Tax Evasion) - Mirra Sri Wahyuni; Diah Khairiyah; Nensi Yuniarti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study is to examine the effect of tax fairness, tax system, tax discrimination, technology and information of taxation on taxpayer perception about the ethics of tax evasion. The data used in this study wereprimary data. The primarydata were obtained from questionnaires distributed to individual taxpayers in Bengkulu City. The number of questionnaires that distributed were 110, but only 108 questionnaires that could be proceed.The data were analyzed by using multiple linear regression analysis with SPSS program.